Islamic Ethical Analysis of Deepfakes and Religious Image Manipulation - Hijriatu Sakinah; Arsy Shakila Putri; Ainur Rofiq (Mahkota Science Publishers, 2025)
When images can replace truth, deepfakes test the limits of trust and authenticity in religion. This study aims to explain the relevance of Islamic ethical principles in assessing digital visual manipulation practices, filling a gap in knowledge in the study of Islamic-based technology ethics. This study uses a qualitative approach with a normative-analytical research design, combined with contextual analysis, an explore the meanings, values, and norms contained in Islamic texts and contemporary social practices. The results state that religious deepfakes create an ethical and knowledge crisis because they make it difficult to distinguish authentic fatwās from fake ones, undermine the foundations of Islamic authority in the form of sanad, integrity ('adālah), and clarity of sources, and violate ṣidq and amānah through tadlīs, ifk, and distortion of meaning that has widespread impacts (mafsadah ‘āmmah) such as radicalisation, sectarian conflict, and a decline in trust in religious institutions. The novelty of this synthesis positions the phenomenon as post-truth religiosity. It proposes a framework of digital authenticity fiqh that goes hand in hand with digital literacy as farḍ kifāyah, so that practical policy responses need to balance the protection of religion with justice and the right to expression through transparent source verification, accountable platform governance, and tabayyun education.